Optimizing integrative cultivation management improves grain quality while increasing yield and nitrogen use efficiency in rice - Hao ZHANG; Dan-ping HOU; Xian-long PENG; Bing-ju MA; Shi-mei SHAO; Wen-jiang JING; Jun-fei GU; Li-jun LIU; Zhi-qin WANG; Yuan-ying LIU; Jian-chang YANG (Journal of Integrative Agriculture, 2019)
A major challenge in rice (Oryza sativa L.) production is to cope with increasing grain yield and fertilizer use efficiency without compromising grain quality. This study was designed to determine if optimizing integrative cultivation management in rice could improve grain quality while increase yield and nitrogen use efficiency (NUE). An indica-japonica hybrid rice cultivar and a japonica rice cultivar were grown in the field, with five cultivation managements including no N application (0 N), local farmer's practice (LFP), and three optimizing integrative cultivation managements, reducing N rate and increasing plant density (ND), ND+alternate wetting and moderate soil drying irrigation (NDW), and NDW+applying rapeseed cake fertilizer (NDWR). The results showed that the optimizing integrative cultivation managements could not only increase grain yield, but also enhance NUE compared to LFP. Compared to LFP, NDWR significantly increased brown, milled, head milled rice rate, ratio of the kernel length to breadth and breakdown value of starch, whereas decreased amylose content, gel consistency, prolamin content, setback value, percentage of chalky kernels, and chalkiness. The three optimizing integrative cultivation managements increased contents of total proteins, albumin and glutelin, activities of the key enzymes involved in the sucrose-starch conversion in grains, root oxidation activity, and malic and succinic acid concentrations in root exudates during the grain-filling period. The results suggested that optimizing integrative cultivation managements could improve grain quality meanwhile increase grain yield and NUE by enhancing physiological activities of rice plants.